Improving the durability of the surveillance monitoring network - Shiyamala, S; Kavitha, T; K. Kowsalya, P (International Journal of Engineering and Technology, 2018)
Wireless sensor network is a distributed network and it comprises a tiny, self directed, low powered device. This paper, investigate the durability of WSN for surveillance monitoring in remote areas. The focus of surveillance machine is to acquire and verify information about enemy capabilities and positions of hostile target.Hence the ability to deploy unmanned surveillance machine by using WSN is of great practical importance for military, because of the energy constraints of sensor devices such network has to be energy aware with the purpose of prolong the lifetime of the network. This paper projected a new protocol called as ZEE-SEP which is formed by combining of operation of EE-SEP and ZSEP based on clustering algorithm in which the durability of the surveillance monitoring network is improved.Â Â